PENERAPAN MODEL PEMBELAJARAN PAIKEM (PEMBELAJARAN AKTIF, INOVATIF, KREATIF, EFEKTIF DAN MENYENANGKAN) - Maujud, Fathul; Nurman, Muhammad; Sultan, Sultan (El-Tsaqafah : Jurnal Jurusan PBA, 2022)
The basic principle of teaching is to guide students' learning activities so that they are willing to learn. Student activity is very necessary in learning activities so that students should be active a lot, because students as subjects are the ones who plan, and they themselves carry out learning. This paper discusses the application of the PAIKEM learning model at MAS Assolihiyah Lopan. While the benefits are as information input for education practitioners (teachers and madrasah principals) regarding the importance of implementing the PAIKEM learning model, and as study material for stakeholders for decision-making references, especially those directly related to the problem of teaching and learning activities in madrasas, especially regarding the application of the PAIKEM learning model in schools. madrasa. The results of this study provide positive implications and impacts for teachers at MAS As-Sholihiyah Lopan, namely understanding the PAIKEM learning model and being able to apply it in the teaching and learning process in the classroom. Although there are still cases of teachers teaching using a conventional approach, namely teaching dominated by the lecture method. Thus, madrasas still need guidance in order to dismantle the teacher-centered teaching paradigm into student-centered learning.